Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3897/bdj.3.e6515
|View full text |Cite
|
Sign up to set email alerts
|

The spatiotemporal pattern of earthworm community in the grass savannas of Lamto (Ivory Coast)

Abstract: BackgroundThe impact of earthworms on both soil physical properties and soil organic matter dynamics has been well documented (Lavelle and Spain 2001). There is a wealth of literature dedicated to the biological mechanisms at work or to empirical approaches based on field data. Assessing the functional role of a species or community implies establishing both time and space scales at which it is effectively the primary determinant of the process(es) at hand. In that context, space-time data analyses are powerfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Ghosh & Mandal (2018) have found that the free-living nematodes can respond to environmental changes in the tropical coasts (Ghosh & Mandal, 2018). The spatiotemporal patterns of earthworm community were shown to indicate different habitats in the coastal grass of West Africa (Rossi & Lavelle, 2015;Jaikishun et al, 2015). Soil fauna were found to exhibit the natural and anthropogenic effects on the west coast of North American, and the most influential natural factors on the abundance and composition of soil fauna were found to be vegetation conditions (David et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ghosh & Mandal (2018) have found that the free-living nematodes can respond to environmental changes in the tropical coasts (Ghosh & Mandal, 2018). The spatiotemporal patterns of earthworm community were shown to indicate different habitats in the coastal grass of West Africa (Rossi & Lavelle, 2015;Jaikishun et al, 2015). Soil fauna were found to exhibit the natural and anthropogenic effects on the west coast of North American, and the most influential natural factors on the abundance and composition of soil fauna were found to be vegetation conditions (David et al, 2016).…”
Section: Introductionmentioning
confidence: 99%